RUANG LINGKUP PENGATURAN PERLINDUNGAN BURUH/PEKERJA MENURUT UNDANG-UNDANG NO.13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Dede Agus (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2019)
The protection of Labour/worker can be enforced by various laws,including Law No. 13 of 2003 on Manpower. This law gives greatattention to the protection of labour/worker, in the terms of substance andscope of regulation, which includes all matters relating to labour at thepre-employment, during and post employment. Therefore, this paper isaimed to discuss the protection of labour/worker according to Law No. 13of 2003 on Manpower in the terms its scope of regulation. The regulatedpre-employment, such as: Manpower Planning and EmploymentInformation, Job Training, Labour Placement and Expansion ofEmployment Opportunities. The regulated during employment, such as:Employment Relationships (work agreements), Protection, Wages andWelfare and Industrial Relations. The regulated post employment, suchas: Termination of Employment and the rights them. Although the scope ofthe regulation is so, it is still not perfect, considering that the law is notperfect. Likewise, if examined in theory the scope of the validity of the law(scope according to time): pre-employment, during and post employmenthas met these criteria, but if examined from the side of purpose theory,character and the nature labor law has not fully fulfilled.